Transdisciplinary Approach In Modern Psychology - Guseltseva, Marina (Զանգակ հրատ.)
The paper looks at key transformations of the contemporary situation requiring new methodological strategies in psychology, and evolution of science in the 20th century from interdisciplinary to trans-disciplinary. The latter takes the form of a strategy for analyzing complex and dynamic phenomena with the help of combined methods and contextual application of research optics borrowed from related disciplines. Methodologically trans-disciplinarily serves as the basis for the integration of cognitive practices and research techniques, development of the holistic outlook, with the expansion of intellectual capacity as its educational side-effect. Conceptually trans-disciplinarily is expressed in several interpretations. Piaget, one of the founders of the approach, viewed it as a higher and more complex stage of integration of knowledge than interdisciplinarity. Contemporary interpretations of trans-disciplinarily vary from emphasizing the fluidity of cognitive space to general principles of cognitive activity seeking mathematical expression. The trans-disciplinary start of contemporary science is characterized by the fact that each discipline is viewed as both a sovereign and open system; development of cognition takes place in the antinomies of tradition and innovation: changes and breakthroughs happen by means of borrowing experience from related disciplines while preserving own scientific identity. Key characteristics of trans-disciplinarily are cognitive movement through disciplines; transparence of disciplinary boundaries: the dissolution of dominant paradigms. Human life space in a transitive society, which is variable, multi-dimensional and complex, can only be understood on the basis of comparison and integration of knowledge within the framework of the transdisciplinary approach.
Keywords: Psychology